Product Search Information System Using Brute Force Algorithm in Website-Based Perfume Store - Fried Sinlae; Bayu Adji Anasyah (Greenation Computer and Information Review, 2024)
The aim of this research is to discuss a product search information system using a brute force algorithm in a website-based perfume shop. Search using a brute force algorithm, where the algorithm is used to search between text patterns in a website-based search. The research method used is the waterfall method, while the data collection method is by conducting interviews and observations. After testing, it was found that the average time was 0.001792355 seconds from 30 keywords resulting in 100% accuracy, thus the application of the brute force algorithm can be used to solve problems in searching for perfume products.